2022
DOI: 10.1186/s12966-022-01310-3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ exposure to and evaluation of food promotions on social media: a multi-method approach

Abstract: Background Traditional food marketing, mostly involving advertisement of nutrient poor and energy dense foods, has the effect of enhancing attitudes, preferences, and increasing intake of marketed foods in adolescents, with detrimental consequences for health. While the use of social media applications in adolescents has proliferated, little is known about the content of food promotions within these applications. The aim of this study was to investigate adolescents’ exposure to and evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
2
9
0
1
Order By: Relevance
“…On the contrary, ads promoting products they do not find appealing or positioned as healthy, were perceived as designed to appeal to other age groups. These results match the categories most frequently promoted to adolescents on Instagram ( 19 ) , as well as those identified as most prevalent in studies assessing adolescent exposure to digital food marketing ( 3 5 , 28 , 29 ) . Repeated exposure to marketing of unhealthy products using content related to adolescents may create social norms around the foods adolescents usually eat, reinforcing adolescents’ unhealthy dietary patterns ( 30 ) .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…On the contrary, ads promoting products they do not find appealing or positioned as healthy, were perceived as designed to appeal to other age groups. These results match the categories most frequently promoted to adolescents on Instagram ( 19 ) , as well as those identified as most prevalent in studies assessing adolescent exposure to digital food marketing ( 3 5 , 28 , 29 ) . Repeated exposure to marketing of unhealthy products using content related to adolescents may create social norms around the foods adolescents usually eat, reinforcing adolescents’ unhealthy dietary patterns ( 30 ) .…”
Section: Discussionsupporting
confidence: 78%
“…Digital media have become a key part of the daily life of adolescents (1) , with such media content exposing them to marketing of ultra-processed products and fast food outlets across a wide range of platforms (2)(3)(4)(5) . Adolescents are highly vulnerable to the persuasive effects of exposure to this type of marketing, although their cognitive skills are similar to those of adults (6,7) .…”
Section: Adolescents Adolescent Targeted Marketing Digital Food Marke...mentioning
confidence: 99%
“…Adolescents are expected to be a specific target group for food marketers due to their increased autonomy to make their food purchases and ability to influence the food purchases of their family, as well as the fact that they constitute future adult consumers (Folkvord et al , 2016; Nöjd et al , 2020; van der Bend et al , 2022a). Recent studies have reported that adolescents are frequently exposed to marketing of ultra-processed products and fast food across several distinct social media platforms (Dunlop et al , 2016; Elliott et al , 2022; Murphy et al , 2020; van der Bend et al , 2022b). However, despite the relevance of the topic, as far as it can be ascertained, few, if any, studies have analyzed the prevalence of digital food marketing targeted at adolescents.…”
Section: Introductionmentioning
confidence: 99%
“… 180 , 181 Research shows that children have difficulties recognizing those tactics and identifying the commercial motives of these messages, because of the involvement of feelings in the advertisements and the blurring line between advertising and entertainment. 182 , 183 Adolescents, in particular, may experience strong relationships with influencers and rather perceive them as friends. Recommendations from influencers, therefore, have greater credibility and authenticity than traditional forms of advertising.…”
Section: Development Of Food Literacy In Children and Adolescentsmentioning
confidence: 99%